Retreat dribble and tight zig-zag combo training: does it affect the improvement of basketball athletes' dribble skills? - Pelamonia, Shandy Pieter; Puriana, Ramadhany Hananto (Tanjungpura Journal of Coaching Research, 2023)
Background and Study Aim. Basketball is one type of sport that is often played by the community, especially among students. In the game of basketball, effective and efficient movements need to be based on the mastery of good basic technical skills. The purpose of this study is to determine the effect of retreat dibble and tight zig-zag combos on improving dribbling to support techniques that aim to get points for basketball athletes.Material and Methods. This study uses a "quantitative" research method with a pseudo-experimental technique, which is research conducted strictly to determine the cause and effect between variables. The sample for this study was 12 athletes from SMPK Santa Maria Kediri. This research design uses a matching-only design. The research instrument used is a basketball dribbling test. Furthermore, the analysis in the study was assisted using the SPSS version 26 application.Results. Hypothesis testing results using a one-sample test with a significance level of 0.05 obtained a value of 0.000 for backward dribbles and 0.000 for tight zig-zag combos. Based on these results, it shows that backward dribble training and tight zig-zag combos provide a significant increase in basketball dribble improvement.Conclusions. Based on the statistical results, it can be concluded that both have an effect on dribbling ability. These results also provide evidence that the combo of retreat dribble and tight zig zag can be applied to train basketball dribbling ability.